2018
DOI: 10.1002/ijch.201800085
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐organic Frameworks Incorporating Multiple Metal Elements

Abstract: The obtaining of materials incorporating multiple metal elements is of interest because the combination of various metal cations results in the achievement of new and enhanced properties. Metal-organic frameworks (MOFs) offer a suitable platform to combine multiple metal elements due to their modular nature and highly controllable structure. The incorporation of various metal elements into MOFs might be accomplished by following different synthetic approaches, which in turn determine the way in which the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 72 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…In UiO-66, in particular, these authors found that while Zr and Hf cations are expected to form a solid solution, Zr/Ti exchange is not energetically favorable -which is in line with experimental findings. 92 Another example was a series of two studies by Sholl 93 and Hayes, 94 on the distribution of metals in MM-MOFs MOF-74 (Mg/Ni) and MOF-74 (Mg/Cd), as well as its impact on water and carbon dioxide adsorption. The authors considered a series of metal ion arrangements as a function of compositionalthough the arrangements considered were not exhaustiveand found that metal mixing was slightly favored over segregation, both energetically and entropically.…”
Section: Distribution Of Metal Centersmentioning
confidence: 99%
“…In UiO-66, in particular, these authors found that while Zr and Hf cations are expected to form a solid solution, Zr/Ti exchange is not energetically favorable -which is in line with experimental findings. 92 Another example was a series of two studies by Sholl 93 and Hayes, 94 on the distribution of metals in MM-MOFs MOF-74 (Mg/Ni) and MOF-74 (Mg/Cd), as well as its impact on water and carbon dioxide adsorption. The authors considered a series of metal ion arrangements as a function of compositionalthough the arrangements considered were not exhaustiveand found that metal mixing was slightly favored over segregation, both energetically and entropically.…”
Section: Distribution Of Metal Centersmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) constitute a class of reticular materials, built up by the combination of metal cations and organic linkers to form extended, crystalline structures. 1 The huge range of possible combinations of metal elements 2 and organic linkers, 3 and their structural variability, make MOFs very versatile materials with application in an extensive variety of fields, such as catalytic applications, 4 gas and hydrocarbon storage 5,6 and separation, [7][8][9][10] electronic sensors 11,12 and water capture 13,14 and adsorption, 15 among others. [16][17][18][19] The use of MOFs in heterogeneous catalysis is particularly interesting as it is possible to attain different metal coordination environments in active solids, thus being possible to modify the activity and selectivity of the resulting catalysts towards a desired reaction.…”
Section: Introductionmentioning
confidence: 99%
“…15 As has been shown recently, mixed-metal MOFs can exhibit very interesting magnetic, optical, and catalytic properties. 69…”
mentioning
confidence: 99%